Perancangan board game untuk meningkatkan kesadaran remaja dalam berlalu lintas - Kumalasari, Linda Dewi; Hapsari, Indri; Sujatmiko, Guguh (Institut Seni Indonesia Yogyakarta, 2024)
The number of car and motorcycle users in Indonesia is increasing from year to year, along with the higher accident rate. The cause of accidents is the vehicle drivers who often violate traffic rules and signs. Due to the lack of adequate public transportation, teenagers are allowed by their parents to drive cars and motorbikes. However, most of these teenagers do not understand traffic well and often end up breaking the rules. Examples of violations include not carrying a SIM and STNK when driving, not wearing a helmet or seat belt, violating traffic signs, and breaking through traffic lights. One method to provide an understanding of traffic to teenagers is through games. Teenagers like communal games such as board games and therefore it is appropriate to apply this method. The purpose of this research is to design a game that can provide an understanding for teenagers to be more aware of the importance of safety in traffic. This research was conducted by distributing questionnaires in advance to find out what teenagers liked. As a result, teenagers like simple objects with colorful shapes. This style is used as a reference in designing a traffic-themed board game.